Students’ Views on Usefulness of Chosen Physics Formulas - PĘCZKOWSKI, PAWEŁ; BŁASIAK, WŁADYSŁAW (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
The study examines students’ opinions on the usefulness of selected physics formulas from the school curriculum. Students have assessed 16 of the most important physics formulas, chosen by physics teachers. Additionally, eye-tracking examinations were performed. For 52 students divided on two groups: not participating in school competitions in physics and other natural sciences and participating in these competitions. Physics contest winners found over 60% of these formulas useful, whereas the average students’ result was less than 30%. The paper also presents the declarations of students, graduating from middle school, concerning their interests in school mathematics, physics, biology and computer science. Students that showed more interest in the selected subjects also perceived the areas of study presented by them to be much more useful to the society. It has also been concluded that the intention of choosing one’s profession within the area of a given subject depends on one’s interest in the subject.